Composition of cuticular waxes coating flag leaf blades and peduncles of Triticum aestivum cv. Bethlehem. (October 2016) - Racovita, Radu C.; Hen-Avivi, Shelly; Fernandez-Moreno, Josefina-Patricia; Granell, Antonio; Aharoni, Asaph; Jetter, Reinhard
Abstract: The work herein presents comprehensive analyses of the cuticular wax mixtures covering the flag leaf blade and peduncle of bread wheat ( Triticum aestivum ) cv. Bethlehem. Overall, Gas Chromatography-Mass Spectrometry and Flame Ionization Detection revealed a wax coverage of flag leaf blades (16 μg/cm 2 ) a third that of peduncles (49 μg/cm 2 ). Flag leaf blade wax was dominated by 1-alkanols, while peduncle wax contained primarily β-diketone and hydroxy-β-diketones, thus suggesting differential regulation of the acyl reduction and β-diketone biosynthetic pathways in the two analyzed organs. The characteristic chain length distributions of the various wax compound classes are discussed in light of their individual biosynthetic pathways and biosynthetic relationships between classes. Along with previously reported wheat wax compound classes (fatty acids, 1-alkanols, 1-alkanol esters, aldehydes, alkanes, β-diketone, hydroxy-β-diketones, alkylresorcinols and methyl alkylresorcinols), esters of 2-alkanols and three types of aromatic esters (benzyl, phenethyl and p -hydroxyphenethyl) are also reported. In particular, 2-heptanol esters were identified. Detailed analyses of the isomer distributions within 1-alkanol and 2-alkanol ester homologs revealed distinct patterns of esterified acids and alcohols, suggesting several wax ester synthases with very different substrate preferences in both wheat organs. Terpenoids, including two terpenoid esters, were present only in peduncle wax. Graphical abstract: Flag leaf and peduncle waxes of Triticum aestivum cv. Bethlehem contained aliphatic, aromatic, and alicyclic compound classes with characteristic chain length and isomer distributions. Benzyl, phenethyl, p -hydroxyphenthyl, and 2-alkanol esters were found present in wheat wax. Highlights: 14 compound classes comprising over 100 structures (including isomers) were identified and quantified. The chain length profiles of all classes were determined and analyzed in light of biosynthetic pathways. Four classes of esters previously unreported in wheat wax comprised 2-alkyl, benzyl, phenethyl and hydroxyphenethyl alcohols. Metamer compositions of 1- and 2-alkanol esters were determined and found to comprise 2-heptanol. Alkylresorcinols and methyl alkylresorcinols included the previously unreported C29 homologs.